2007
DOI: 10.1007/s10895-007-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Interpretation of Tryptophan Fluorescence

Abstract: Origin of tryptophan fluorescence is still up to these days a quiz which is not completely solved. Fluorescence emission properties of tryptophan within proteins are in general considered as the result of fluorophore interaction within its environment. For example, a low fluorescence quantum yield is supposed to be the consequence of an important fluorophore-environment interaction. However, are we sure that the fluorophore has been excited upon light absorption? What if fluorophore excitation did not occur as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 10 publications
6
17
0
2
Order By: Relevance
“…The same results were obtained when interaction between calcofluor white and β-lactoglobulin was studied and where the authors showed that protein emission occurs from Trp 19 residue [33]. Absence of emission of Trp 61 residue of β-lactoglobulin could be explained by the fact that this tryptophan is not excited as the result of its close interaction with disulfide bridge or any other amino acids [34]. At neutral pH, β-lactoglobulin and OBP are dimers.…”
Section: Results and Discusssionsupporting
confidence: 60%
“…The same results were obtained when interaction between calcofluor white and β-lactoglobulin was studied and where the authors showed that protein emission occurs from Trp 19 residue [33]. Absence of emission of Trp 61 residue of β-lactoglobulin could be explained by the fact that this tryptophan is not excited as the result of its close interaction with disulfide bridge or any other amino acids [34]. At neutral pH, β-lactoglobulin and OBP are dimers.…”
Section: Results and Discusssionsupporting
confidence: 60%
“…2). The two shortest lifetimes correspond to what we can usually observe for Trp residues in protein or for free tryptophan in solution [11], while the longest lifetime is the result of the interaction of the Trp residue within its environment. The mean fluorescence lifetime (¼ 4.788 ns), calculated from two experiments and measured at 340 nm, was used to measure the rotational correlation of the Trp residues from the Perrin plot.…”
Section: Methodssupporting
confidence: 63%
“…The two shortest fluorescence lifetimes (0.8 and 2.7 ns) are in general found in most proteins and for free tryptophan in solution. Thus, these two fluorescence lifetimes emanate from structural rearrangements of Trp residue in the excited state independent of the tryptophan microenvironment [11]. Nevertheless, the three lifetimes increase with the emission wavelengths in the same way, the longest lifetime increases from 4.8 ns at 310 nm to 8 ns at 370 nm and the middle lifetime increases from 1 to 2 ns in the same range of emission wavelength.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Excitations were performed both at 280 nm and 295 nm, where emissions reflect the contribution of all aromatic amino acids or only that of Trp residues, respectively [31]. Results showed (Fig.…”
Section: Quenching Of Intrinsic Agp Fluorescencementioning
confidence: 96%